Characterization of leaves and fruits of mango (Mangifera indica L.) CV. IMBU - Vieccelli, Juliana Cristina; Siqueira, Dalmo Lopes de; Bispo, Wilka Messner da Silva; Lemos, Lorena Moreira Carvalho (Revista Brasileira de Fruticultura, 2015)
Although mango is one of the tropical fruits of greater interest in the world trade, literature concerning their rootstocks (characteristics and utilization) is scarce. This study aimed to characterize mango plants from cv. Imbú, widely used as rootstock in the Zona da Mata region, State of Minas Gerais (MG), Brazil. Though fruits of this cultivar do not present desirable commercial characteristics, this study allowed us to characterize part of plant morphology and fill a gap in the literature, providing subsidies for future investigations. For such, 'Imbú' plants (˜ 4-years old) from the collection of the Universidade Federal de Viçosa, located in Viçosa -MG were evaluated. The descriptors were: (i) leaf blade division;(ii) leaf composition; (iii) petiole length in relation to leaf blade; (iv) phyllotaxis, (v) leaf position in relation to the branch insertion; (vi) leaf shape; (vii) leaf apex and base angles; (viii) leaf margin category; (ix) venation; (x) leaf length and thickness; (xi) leaf length/thickness ratio; (xii) leaf texture; (xiii) leaf fragrance; (xix) leaf color. The leaves were depicted as lanceolate, with entire margins and sharp angles at the base and apex of the leaf blade. The intensity of the green color of the leaf blade was considered intermediate and the abaxial surface staining showed less intense than that observed in the upper side. The fruits were processed and separated into peel, pulp and seeds in order to evaluate the flesh color, fresh weight and percentage of seeds, peel and pulp. It was determined the soluble solids content, starch concentration, the peel and the pulp color, the cerosity, the percentage evaluation of peel, pulp and seed and the pulp firmness. The average number of germinated seedlings per seed was estimated for 230 sown seeds.

Apesar de a manga ser uma das frutas tropicais de maior interesse no comércio mundial, a literatura sobre os seus porta-enxertos (características e utilização) é escassa. Este estudo teve como objetivo caracterizar as mangueiras da cv. Imbu, amplamente utilizada como porta-enxerto na região da Zona da Mata de Minas Gerais (MG), Brasil. E, embora frutos dessa cultivar não apresentem características comerciais desejáveis, este estudo permitiu caracterizar parte da morfologia da planta e preencher uma lacuna na literatura, fornecendo subsídios para futuras investigações. Para tal, folhas completamente expandidas da porção mediana de ramos expostos à luz solar e frutos plenamente desenvolvidos foram coletados de plantas da cv. 'Imbu' (˜ 4 anos de idade) da coleção da Universidade Federal de Viçosa, localizada no município de Viçosa - MG. Os descritores foram: (i) divisão lâmina de folha; (ii) a composição da folha; (iii) comprimento do pecíolo em relação à lâmina de folha; (iv) filotaxia, (v) a posição das folhas em relação à inserção do ramo; (vi) a forma de folha; (vii) ângulos do vértice da folha e de base; (viii) categoria margem da folha; (ix) venação; (x) comprimento da folha e espessura; (xi) Relação espessura / comprimento da folha; (xii) textura da folha; (xiii) fragrância da folha; (xix) cor da folha. As folhas foram descritas como lanceoladas, com margens inteiras e ângulos afilados na base e ápice da lâmina de folha. A intensidade da cor verde da lâmina foliar foi considerada intermediária e a coloração da superfície abaxial mostrou menos intensa do que a observada no lado superior. Os frutos foram processados e separados em casca, polpa e sementes, a fim de avaliar a cor da polpa, o peso fresco e percentagem de sementes, casca e polpa. Foi determinado o teor de sólidos solúveis, concentração de amido, coloração da casca e da polpa, a cerosidade, a percentagem de casca, de polpa e de semente e a firmeza da polpa. O número médio de plântulas germinadas por semente foi estimado para 230 sementes semeadas.
Keywords: Rootstock; Mangifera indica; Morphology